The geometries of Afro Asia art beyond solidarity - Kee, Joan (University of California Press, 2023)
"How do we embark on a history of art that proceeds from the assumption of a global majority? Taking as a rhetorical departure the construct of Afro Asia which doubles as both an ontological reference and an epistemological intervention, this book centers the worlds Black and Asian artists initiate through their work. Afro Asia breaks down delineated time into points, trajectories, angles, magnitudes and relative positions so that temporality and chronology figure primarily as questions of geometry: it asks if and how we can we be something other than what biology, politics, culture, and economics tells us we are or must become. Spanning North America, Europe, Asia, and Africa, this book challenges the institutionalization of contemporary art as a global enterprise increasingly governed by the judgments of a self-selecting minority"--
Keywords: Geschichte; Kunst; Globalisierung; Kunstgeschichte -- Fach; Afrika; Asien; Art, Comparative; Art and race; Artists, Black / Asia; ART / General; Artists, Black; Asia